Modeling the relationship between depression in people with cancer and perceived stress, with the mediating role of eating problems, sexual satisfaction, emotion regulation and self-compassion - Moniri, Reihaneh; Gharraee, Banafsheh; Zahedi Tajrishi, Komeil (Frontiers in Psychology, 2024)
Aim With the rising prevalence of cancer and the adverse physical and psychological experiences endured by affected individuals, this study aims to establish a model illustrating the relationship between depression in people with cancer and perceived stress. Additionally, it examines the mediating influence of eating problems, sexual satisfaction, emotional regulation, and self-compassion. Method This study employs a descriptive-correlational research method, utilizing structural equation analysis (modeling) to explore the role of mediators. The research sample comprised 200 individuals diagnosed with cancer, selected based on predetermined inclusion and exclusion criteria. Participants completed Beck’s 13-item depression questionnaire, a 10-item perceived stress questionnaire, an 8-item appetite measurement questionnaire, a 25-item sexual satisfaction questionnaire, a 10-item emotion regulation questionnaire, and a 12-item compassion questionnaire. The data were subsequently analyzed using SPSS-24 and Lisrel 80/8 software. Findings The research findings indicate a significant positive relationship between perceived stress and depression in people with cancer. Furthermore, eating problems exhibited a mediating role in the relationship between perceived stress and depression, with a direct effect coefficient of (t = 0.28, ß = 0.02). However, the path from perceived stress to depression, mediated by sexual satisfaction, was found to be statistically insignificant, with a standard coefficient of 0.01 at the p < 0.05 level. Emotion regulation demonstrated a direct effect coefficient of (t = −3.52, ß = –0.33) on depression. Likewise, self-compassion exhibited a direct effect coefficient of (t = −3.08, ß = –0.28) on depression, while the path from perceived stress to depression was mediated by self-compassion, with a standard coefficient of 0.12 at the p < 0.05 level. Conclusion In conclusion, this study sheds light on the interplay between depression and perceived stress in individuals with cancer, revealing a significant positive association. Eating problems emerged as a mediating factor, directly influencing the manifestation of depressive symptoms. However, the mediation pathway through sexual satisfaction was found to be statistically insignificant. Emotion regulation and self-compassion were identified as influential factors, with direct effects on depression and self-compassion also serving as a mediator in the relationship between perceived stress and depression. The findings emphasize the importance of targeted interventions addressing eating problems, enhancing emotion regulation, and fostering self-compassion to alleviate the impact of depression and perceived stress in individuals facing cancer-related challenges. Further research is encouraged to refine and expand upon these insights, advancing holistic care for this population.